INFLUENCE OF FINANCIAL PERFORMANCE ON THE VALUE OF COMPANIES WITH ISLAMIC SOCIAL REPORTING AS A MODERATION VARIABLE (Case Study on Islamic Banking Companies in Indonesia-Malaysia 2015-2019) - Erisa Putri Wardani; Puji Nurhayati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of financial performance on the value of companies by using Islamic Social Reporting as a moderation variable. The study used a regression analysis technique of panel data with E-views software from a sample of 13 Indonesian Islamic banks and 6 Malaysian Islamic banks in the period 2015-2019. The results of this study can conclude that there are several variable differences in Indonesian and Malaysian Islamic banks. In Indonesian Islamic banks, financial performance significantly affects the company's value, but in Malaysian Islamic banks, financial performance does not significantly affect the company's value. Then both Indonesian and Malaysian Islamic banks proved that Islamic Social Reporting could not moderate the relationship between financial performance and the company's value. Further research can add other research variables that can affect a company's value apart from financial performance. Keywords: Islamic social reporting, financial performance, company values, Islamic banking.